THE EFFECTIVENESS OF USING ANIMATION MOVIE IN IMPROVING SPEAKING SKILLS OF ELEMENTARY STUDENTS - Hasti Nuansari; Widi Sriyanto (ELLTER Journal, 2021)
This research aimed to prove the effectiveness of using animation movie in improving speaking ability of elementary students. The research was conducted in one class of the fourth grade with twenty-nine students and the selected samples were taken by random sampling. The data collection used an oral test as it is an experimental research by using T-test at 0.05 significance level. The results showed that the score of t-observation (to) was 9.43. Moreover, on the 0.05 significance level and with df n-1=28 the score of t-table (tt) was 1.70. It appears to > tt (9.43 > 1.70). It can be concluded that using animation movie in teaching speaking was effective for the elementary students. Benefits of the research result were by using animation movie the students could be more confident to speak with others because animation movies had interesting content that made the students interested to retell the animation movie with their own sentences. Therefore, they could be easier to make their own visualization with the movies which they had watched. However, it would be better if a language teacher gives many chances to practice in the classroom along with interesting media.